The Incidence and Cost of Job Loss in a Transition Economy: Displaced Workers in Estonia, 1989-1999 - Hartmut Lehmann; Kaia Phillips; Jonathan Wadsworth (Institute for the Study of Labor (IZA), 2002)
We examine the pattern and costs of worker displacement in one of the more reform-oriented transition countries, Estonia, as the transition process develops. Using Labour Force Survey data covering the period 1989-1999, we show that after the initial shock, displacement rates in Estonia have fallen back to levels observed in several western economies, as the economy picks up. The incidence of displacement is also similar to that in the West – concentrated on the less skilled and those with short job tenure. Roughly half of those displaced find re-employment within two months while the other half lingers on in the state of non-employment. There is less evidence however of a wage penalty to job loss, unlike in some Western countries, a fact one might attribute more to the nature of the transition process than to wage setting institutions in Estonia. The main cost of displacement is then the income loss due to non-employment, which is severe for a minority of workers who experience long-term non-employment.
Keywords: P50; J65; J64; 330; displaced workers; labour markets in transition; Kündigung; Arbeitslosigkeit; Arbeitsmobilität; Lohn; Übergangswirtschaft; Schätzung; Estland